Investigation of Teaching Self-Efficacy and Cognitive Flexibility Among Novice Teachers from Two-Year and Four-Year Training Models - Samol OL Nguon; Hart Bunhe; Meak Chantheng (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study examined teaching self-efficacy and cognitive flexibility of Cambodian secondary schools’ novice teacher from two-year training and four-year training model. It aims to understand whether the four-year model significantly outperforms the two-year model in fostering these psychological traits that is essential for future policy decisions and the long-term success of the nation’s education reforms. Methodology: Utilizing a quantitative research design, data were collected from 313 teachers through validated surveys measuring these constructs, and analyze via statistical methods including confirmatory factor analysis, comparison and regression. Main Findings: Finding revealed that the four-year model more effectively enhances teachers’ teaching self-efficacy and cognitive flexibility than two-year model. Teaching self-efficacy positive relates to cognitive flexibility, especially for instructional strategies and student engagement. Meanwhile classroom management shows no difference. Two-year graduates report higher control while four-year graduates perform better on alternatives subscales. This highlights training duration effects on novice teachers’ development outcome. Novelty/Originality of this study: This study adds to the existing literature, indicating that teaching self-efficacy and cognitive flexibility of novice teachers from two different training models were significantly difference. Additionally, the study highlights the need for teacher education reforms to foster greater confidence and flexibility among teachers, thereby improving instructional quality in Cambodia’s evolving education system.